Efektivitas Program Bantuan Tunai Bersyarat Mengatasi Kemiskinan dan Kelaparan - Lailul Mursyidah (Universitas Muhammadiyah Sidoarjo, 2017)
This research aims to analyze the effectiveness of conditional cash transfer programs in reducing poverty and hunger. This qualitative descriptive research is located in Kabupaten Temanggung, Central Java. Data obtained from interviews, observation and documentation. The selection of informants was done by purposive sampling technique. Informants in this research is the head of social assistance of Dinas Sosial Kabupaten Temanggung as the head of UPPKH Kabupaten Temanggung. Data analysis technique using Miles & Huberman’s interactive model. The results of this research indicate that after 2 years implementation of Program Keluarga Harapan (PKH) as conditional cash transfer program in Kabupaten Temanggung, the output has not been achieved. Seen from before and after implementation of PKH, there is no different in nutrition status of infants and toddlers as well as the family welfare. The progress is almost the same, still in a constant state before and after PKH implemented. The condition show that the conditional cash transfer program in Kabupaten Temanggung has not been effective in eradicate poverty and hunger.